2021
DOI: 10.1021/acs.jafc.1c02410
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthetic Mechanism of Key Volatile Biomarkers of Harvested Lentinula edodes Triggered by Spore Release

Abstract: In this study, headspace solid-phase microextraction-gas chromatography−mass spectrometry, multivariate analyses, and transcriptomics were used to explore the biosynthesis of key volatiles and the formation of spores in Lentinula (L.) edodes. Among the 50 volatiles identified, 1-octen-3-ol, phenethyl alcohol, and several esters were considered key aromas because of their higher odor activity values. Eleven volatiles were screened as biomarkers by orthogonal partial least squares discriminant analysis, and hier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…It was visually observed that a higher alcohol content was associated with a lower aldehyde content in the various strains of F. filiformis , which is related to alcohol dehydrogenase activity [ 33 ]. In the future, clarifying the regulatory genes of aroma compounds in edible mushrooms would be crucial in cultivating cultivars of F. filiformis with more appealing scents for consumers [ 35 ]. The concentrations of acids, aldehydes, and esters showed a consistent trend, peaking in F2 and having lower values in F1 and F3.…”
Section: Resultsmentioning
confidence: 99%
“…It was visually observed that a higher alcohol content was associated with a lower aldehyde content in the various strains of F. filiformis , which is related to alcohol dehydrogenase activity [ 33 ]. In the future, clarifying the regulatory genes of aroma compounds in edible mushrooms would be crucial in cultivating cultivars of F. filiformis with more appealing scents for consumers [ 35 ]. The concentrations of acids, aldehydes, and esters showed a consistent trend, peaking in F2 and having lower values in F1 and F3.…”
Section: Resultsmentioning
confidence: 99%
“…This is consistent with the results that phenylethyl alcohol was detected in all FMPs except Pp4‐FMP. However, phenylacetaldehyde was only detected in Ll1‐FMP, which may be due to the different transcription levels of the genes encoding aryl‐alcohol dehydrogenase leading to complete or incomplete conversion of phenylacetaldehyde (Sun et al., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The production of 1-octen-3-ol in the postharvest fruiting bodies of L. edodes continued to decrease. Five LOX-related genes were identified from the transcriptomes in the postharvest fruiting bodies of L. edodes , the expression levels of one in which were positively correlated with 1-octen-3-ol, indicating that one of the LOX genes was responsible for regulating the biosynthesis of 1-octen-3-ol [ 64 ].…”
Section: Discussionmentioning
confidence: 99%